Management of arrhythmic storm: What is its clinical signifcance? - Ruiz Hernandez, Gabriel Fernando (2024)
Arrhythmic storm is characterized by the occurrence of three or more distinct episodes of ventricular tachycardia or ventricular fibrillation within a 24-hour period, posing a signifcant risk for cardiovascular complications and resulting in high morbidity and mortality. The objective of this review article is to provide recommendations for the management and pharmacological treatment with the greatest impact on patients with arrhythmic storm, based on the latest global literature. A literature search was conducted in the PubMed and Scielo databases,focusing on updated and relevant articles in English or Spanish published within the last 10 years, detailing the clinical signifcance of arrhythmic storm, its implications, and therapeutic approaches. This condition is multifactorial, highlighting the importance of timely diagnosis to control the triggering cause. Given its high recurrence and mortality rates, patients must be closely monitored in an intensive care unit. The management of arrhythmic storm is a current challenge, as it involves a clinical situation with both early and late high mortality. The most important techniques for addressing this condition include antiarrhythmic pharmacological treatment, defbrillator programming, and catheter ablation.